Efectiveness of Problem Based Learning Models by Using E-Learning and Learning Motivation Toward Students Learning Outcomes on Subject Circullation Systems - Lamria Tambunan; Rusdi Rusdi; Mieke Miarsyah (Indonesian Journal of Science and Education (IJOSE), 2018)
The development of technology-based learning today is growing rapidly, the use of which combines the computer with the network is a growing up. One of them is e-Learning. By combining the use of eLearning with Problem Based Learning model and motivation is expected to be effective in improving learning student’s outcomes of circulatory material. Learning is not merely media or model, but motivation has an effect on learning. This research was conducted to measure the effect of PBL model applied with e-Learning and motivation to student outcomes. The method of research is Quasi Experiment with Two Way Anova Design. This study was conducted at SMPK St. Paulus Jakarta in May-June 2017. The data showed normal and homogeneous values (p> 0.05) with a sample size of 30 people. Result of research using two way anova test got data that p value = 0.000, mean p <0.05 (reject H0). The conclusion is that (1) there is influence of PBL model by using e-Learning to student outcomes, (2) there is influence of motivation to student outcomes, and (3) there is interaction between PBL using e-Learning and motivation to student outcomes.Keywords: e-Learning, motivation, problem based learning, student learning out comes